EVALUATING THE CONTRIBUTION OF PHYSICIANS IN THE MULTIDISCIPLINARY RESPONSE TO THE COVID-19 PANDEMIC: A COMPREHENSIVE REVIEW - Ali Abdulrahman Ali Refaei, Amer Omar Nasser Alali, Abdulaziz Mohamed Qasim Safhi, Akram Ahmed Wafi, Abdullah Saad Alsaleem, Abdullah Saad Alsaleem, Faisal Abdullah Alamri, Saleh Gazai Alotaibi, Fahad Khulyf Alaenezi, Yahya Omar Ali Hazazi, ,; Salem Nasser Salem Al-Qahtani, Basem Saud Ahmed Farhan, Abdulrahman Mohammed Abdulaziz Alarifi, Amjad Naji M Almotiri, Maali Eidan Mufdi Aldhafeeri, Dr Abdul Aziz Dobyan Alfaim, (Chelonian Research Foundation, 2022)
The COVID-19 pandemic has posed a significant threat to healthcare systems globally, affecting several levels of operation. Available research indicates that the moral challenges encountered by doctors during these extraordinary times have positioned them at the crossroads of ethical and unethical issues. This occurrence has raised concerns about the ethical principles of doctors and how it has influenced their behavior. The objective of our study is to explore the range of changes in the field of patient care optics during the epidemic and how these changes have affected the mental well-being of doctors. We conducted a search in databases such as PubMed/Medline, Web of Science, Scopus, Science Direct, CINAHL, and PsycInfo using a predetermined search query. The titles and abstracts that were obtained were examined. Subsequently, a comprehensive examination of the papers that met our specific criteria for inclusion was conducted. This scoping research reveals a concerning increase in psychological suffering, moral harm, cynicism, doubt, fatigue, and bereavement among doctors during the epidemic. Allocation of resources and provision of medical treatment were primarily governed by the principles of rationing, triaging, taking into account factors such as age, gender, and life expectancy. Inadequate professional controls and institutional services may have contributed to the decline in doctors' well-being. This study emphasizes the need to address the declining mental health and to reinstate the medical profession's commitment to promoting fairness and equal treatment. Keywords: COVID-19, doctor, mental health, individual wellness, professional conduct